Relation of Multiple Inflammatory Biomarkers to Incident Atrial Fibrillation - Schnabel, Renate B.; Larson, Martin G.; Yamamoto, Jennifer F.; Kathiresan, Sekar; Rong, Jian; Levy, Daniel; Keaney, John F.; Wang, Thomas J.; Vasan, Ramachandran S.; Benjamin, Emelia J. (The American journal of cardiology, 2009)
Basic and clinical studies have suggested that inflammation predisposes to atrial fibrillation (AF). We assessed the association of 12 circulating inflammatory biomarkers (i.e., C-reactive protein, fibrinogen, interleukin-6, intercellular adhesion molecule-1, lipoprotein-associated phospholipase A2 [mass and activity], monocyte chemoattractant protein-1, myeloperoxidase, CD40 ligand, osteoprotegerin, P-selectin, and tumor necrosis factor receptor II) with incident AF in 2863 Framingham Offspring Study participants (mean age 60.7 years, SD = 9.4, 55% women). During follow-up (median 6 years), 148 participants (43% women) developed incident AF. In the multivariable proportional hazards models, the inflammatory biomarker panel was associated with incident AF (p = 0.03). With stepwise selection (p <0.01 for entry and retention), log-transformed osteoprotegerin was associated with incident AF (hazard ratio per SD 1.30, 95% confidence interval 1.08 to 1.56, p = 0.006). Adjusting for interim myocardial infarction or heart failure attenuated the association between osteoprotegerin and incident AF (hazard ratio 1.18, 95% confidence interval 0.98 to 1.43, p = 0.09). In conclusion, circulating osteoprotegerin concentration was significantly associated with incident AF in our community-based sample, possibly mediated by interim cardiovascular events.